Farkas-Type Theorems and Applications: From IPH Functions to ICR Functions. (18th November 2018) - Momenaei Kermani, V.; Doagooei, A. R.
Abstract: Some versions of Farkas-type theorems for systems of inequalities consisting of Increasing and Positively Homogeneous (IPH) functions are established. Applying these results, we establish Farkas-type theorems for the systems involving Increasing and Coradiant (ICR) functions as well. As an application, we apply these results to solve constrained IPH and ICR optimization problems with unconstrained counterparts.